PENERAPAN NILAI PENDIDIKAN AKHLAK DALAM KITAB AL BARZANJI DI MADRASAH TSANAWIYAH ROUDLATUL ULUM KARANGPLOSO MALANG - Lukman Hakim; Mohammad Afifulloh; Muhammad Sulistiono (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
Moral education is an activity or conscious effort that is carried out intentionally to provide guidance, both physically and spiritually, through the cultivation of values, moral and physical training and produces positive changes that can later be actualized in life, with habits of behaving, thinking. and noble character towards the formation of humans who have personalities or traits inherent in the human soul. his study aims to describe the application of moral education values in Al Barzanji at MTs Raudlatul Ulum (Case Study of MTs Raudlatul Ulum Karangploso). With research focus: 1). What is the model for inculcating the value of moral education in the book of al-Barzanji at MTS Raudlatul Ulum Karangploso? 2). How is the method of applying the values of moral education in the book of al-Barzanji at MTS Raudlatul Ulum Karangploso? This exploration utilizes a subjective methodology with unmistakable examination type. The information assortment technique utilized was observation, interviews and documentation. Information investigation strategies in this examination incorporate information assortment, information decrease, information show, reaching determinations. checking the legitimacy of the information through tireless perception, triangulation, and furthermore peer checking through conversation. The conclusion of this study is a model of applying moral values at MTs Roudlatul Ulum namely teachers according to educational qualifications, mastering learning materials, time discipline. model of applying the values of moral education individually, socially. Kata Kunci : Nilai, Pendidikan Akhlak, kitab al barzanji